Mitigation tools and politeness strategies in invitation refusals: American and Russian communicative cultures - Angela V. Litvinova; Tatiana V. Larina (Peoples' Friendship University of Russia (RUDN University), 2023)
The performance of speech acts varies widely across cultures due to differences in values, communicative norms and traditions as well as politeness strategies. This can cause problems in communication and lead to sociopragmatic failures. This paper aims to discover potential linguistic and sociocultural differences in refusal to invitations performed by Americans and Russians in interpersonal interaction. It explores the variations in the performance of refusal in terms of form (direct vs. indirect), length, face-saving moves/semantic formulas and politeness strategies in the contexts differed in social and power distance. The data were obtained through a Discourse Completion Task (DCT) with 120 participants (50 Americans and 70 Russians) and analysed drawing on Cross-Cultural Pragmatics, Speech Act Theory, Theory of Politeness and Cultural Studies with the implementation of contrastive qualitative and quantitative analysis. The findings revealed some differences in the role of social factors in the realisation of refusals, while the most salient factor appears to be that of cultural context. Despite some obvious similarities in the performance of refusal in its form, miti- gation moves and politeness strategies, American refusal demonstrated a tendency to be more indirect and verbose, conventionally accompanied by a positive emotive adjunct aimed at enhancing the positive face of interlocutors. The findings showed that Americans use Positive and Negative politeness strategies with more regularity and thus do more facework aimed at mitigating the possible negative effect of this dispreferred act. The Russians, by contrast, used politeness strategies with less regularity, in some cases resorted to directness and were more focused on the clarity of their response to invitation rather than considerations of face. The findings are consistent with communicative values and politeness in the two cultures. They can contribute to the systematisation of culture-specific features of interpersonal interaction in American and Russian contexts and the description of communicative ethno-styles.